Hemophagocytic Lymphohistiocytosis Gene Mutations in Adult Patients Presenting With CLIPPERS-Like Syndrome. Issue 3 (May 2021) - Taieb, Guillaume; Kaphan, Elsa; Duflos, Claire; Lebrun-Frénay, Christine; Rigau, Valérie; Thouvenot, Eric; Duhin-Gand, Emeline; Lefaucheur, Romain; Hoang-Xuan, Khe; Coulette, Sarah; Ouallet, Jean Christophe; Menjot de Champfleur, Nicolas; et al.
Abstract : Objective: To determine whether adult cases of Chronic Lymphocytic Inflammation with Pontine Perivascular Enhancement Responsive to Steroids (CLIPPERS) may be related to familial hemophagocytic lymphohistiocytosis (HLH) causes, we have screened patients with adult-onset CLIPPERS for mutations in primary HLH-associated genes. Methods: In our cohort of 36 patients fulfilling the criteria for probable or definite CLIPPERS according to the CLIPPERS-2017 criteria, we conducted a first study on 12 patients who consented to genetic testing. In these 12 patients, systemic HLH criteria were searched, and genetic analysis of 8 genes involved in primary HLH was performed. Results: Four definite and 8 probable CLIPPERS were enrolled (n = 12). Mutations involved in HLH were identified in 2 definite and 2 probable CLIPPERS (4/12). Three of them had biallelic PRF1 mutations with reduced perforin expression in natural killer cells. The remaining patient had biallelic UNC13D mutations with cytotoxic lymphocyte impaired degranulation. None of the mutated patients reached the criteria for systemic HLH. During follow-up, 3 of them displayed atypical findings for CLIPPERS, including emergence of systemic non-Hodgkin lymphoma (1/3) and confluent gadolinium-enhancing lesions on brain MRI (3/3). Conclusions: In our patients presenting with adult-onset CLIPPERS, one-third have HLH gene mutations. This genetic treatable condition should be searched in patients with CLIPPERS, especially in those presenting with atypical findings.